Partnership at play: empowering Student Partners to navigate third space - Karen Arm (Journal of Learning Development in Higher Education)
Solent Student Partner Programme is a cross-institutional, third-space project led by the central Education Office at Southampton Solent University in the UK. This case study discusses how we have used kinaesthetic play to support our Student Partners to articulate and negotiate the challenges of third-space partnerships. It starts by outlining our Student Partner Programme in the context of the third-space partnership literature. Then it describes the Play-Doh method that we used to support students to reflect on their identity and experiences as third-space partners. The case study concludes by arguing that play provides an empowering tool for students (and staff) to mould third-space partnerships together.